The role of Instagram in creating brand awareness among the millennial skate culture of Cape Town. - Blommaert, Karel (The IIE, 2016)
The study investigates the role of Instagram in creating brand awareness among the millennial skate culture of Cape Town. Interviews were administered to a sample group of 11 millennials in accordance with a qualitative ethnographic research design. The study aims to highlight the amplifying effect that the internet has on word-of-mouth about fashion brands, as well as the effect that using this unconventional marketing approach has on the brand’s image and overall demand from consumers. Lastly, the study highlights the positive effects that word-of-mouth marketing has on a brand and its image, while demonstrating why traditional advertising lacks these positive effects on brand’s images. The study found that Instagram allowed people to be aware of a group of brand loyals, which in turn caused them to want to be a part of the niche fashion group too.
Keywords: Brand awareness; Ethnographic research; Marketing